mtDNA and microsatellite_data - Miller, Mark P.; Haig, Susan M.; Mullins, Thomas D.; Ruan, Luzhang; Casler, Bruce; Dondua, Alexei; Gates, H. River; Johnson, J. Matthew; Kendall, Steve; Tomkovich, Pavel S.; Tracy, Diane; Valchuk, Olga P.; et al. (Dryad Digital Repository, 2014)
A zip file containing two data files plus a third text file containing descriptions of the data files. See file "File annotations.txt" included int the archive for more information.